Child abuse in Pakistan: A qualitative study of knowledge, attitudes and practice amongst health professionals. (February 2019) - Maul, Kayleigh M; Naeem, Rubaba; Rahim Khan, Uzma; Mian, Asad I; Yousafzai, Aisha K; Brown, Nick
Abstract: Child abuse is a global problem and pervades all cultures and socio-economic strata. The effects can be profound and life altering for victims. There is substantial literature from high income countries about signs of abuse, but a dearth of data from low and middle income countries like Pakistan. Healthcare professionals (HCP) are ideally placed to detect abuse, but, to inform interventions, an understanding of their experiences, training needs and cultural beliefs is needed. This study aimed to: (1) Explore the challenges that HCP face when managing cases of abuse; (2) Explore cultural beliefs and understand how these shape practice and (3) Identify training needs. A qualitative study using a phenomenological design was conducted. In-depth interviews were conducted with doctors, nurses and security staff in the emergency department of a large private hospital in Pakistan (n = 15). Interviews were undertaken in Urdu, translated into English and analysed using an inductive thematic approach. Multiple challenges were identified. The process of referral to legal services was poorly understood and further training and guidelines was suggested by participants. As the legal system in Pakistan does not allow HCP to keep potentially abused patients in their custody, they felt restricted in their ability to advocate and concerned about the safety of both the identified children and themselves. HCP have potential to detect abuse early; however, in Pakistan there are numerous challenges. HCP require support through training, as well as clear institutional frameworks and legal support to undertake this role.